Surgical site infection among gynecological group: risk factors and postoperative effect - Bharatnur, Sunanda; Agarwal, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was carried out to evaluate the preoperative and intraoperative risk factors associated with surgical site infection amongst gynecology patients and its impact on postoperative recovery. Methods: A prospective, observational study was conducted among 285 patients Who underwent surgery over a period of two years. Diagnosis of SSI was made as per CDC criteria. Various risk factors and impact of SSI on postoperative recovery were analysed. Statistical analysis was carried out with SPSS version 16.0. Range and mean was calculated for continuous variables and overall incidence rate of SSI is also calculated. Pearson Chi-square test was used to test risk factor association with SSI. Odds ratios and 95% confidence intervals (CI) was calculated. Significance was assumed at a p value of less than 0.05. Results: The incidence of SSI was found to be 52 out of 285 women (46%). Majority of SSI, i.e. 49 out of 52 (94%) were superficial in nature. Deep SSI was seen in 3 patients (6%). No organ/space infection was noted in any patient. Women who were over 50 years had higher risk of developing SSI than women between 36 to 50 years (OR 0.519 Vs 0.214). The risk of SSI was 4 times in case of clean contaminated wounds as compared to clean wounds (OR 3.877). The risk further increased to 7 times in case of dirty wounds (OR 6.753). Other risk factors which are significantly associated with SSI were BMI (p value <0.001), midline incisions (p <0.001) and Mattress suture (p <0.001). Presence of previous scar had intraoperative adhesions, weaker scar and poor healing which predispose to development of SSI. Comorbidities which influence SSI’s in the present study are diabetes mellitus (OR 5.49, 95% CI 2.506-12.066, P <0.001), anaemia (OR 4.63, Cl 2.458-8.756) and hypertension (OR 2.46, Cl 0.994-6.117). Wound swab was sterile in 33(63%) cases and 18(35%) cases showed growth of the organism. Most common organism noted was E. coli 9 (50%) followed by Klebsiella and Staph aureus. Conclusions: SSIs are increasing in the current scenario due to increase in the number of surgeries, however they can be prevented by early identification and optimization of medical comorbidities and BMI. Meticulous preoperative workup and intraoperative surgical steps are important in reducing the risk of developing SSI. A decrease in infection rate can lead to substantial reduction in the burden of disease.